Information, technology, and market rewards: Incentivizing aflatoxin control in Ghana - Magnan, Nicholas; Hoffmann, Vivian; Garrido, Gissele; Kanyam, Daniel Akwasi; Opoku, Nelson (Elsevier, 2021)
The quality of agricultural products can affect both farm incomes and the healthfulness of farm families’ diets. However, many quality attributes are difficult to observe, making it difficult for farmers to learn how to improve the quality of their crops. Lack of premium pass-through and the cost of quality-enhancing inputs are additional barriers to improving output quality. In this paper, we examine the relative importance of each of these barriers to smallholder adoption of technologies for reducing aflatoxin, a common food safety hazard. We conduct a randomized controlled trial in northern Ghana over the course of two seasons to test how three interventions affect adoption of practices that reduce aflatoxin risk as well as aflatoxin levels in groundnuts: (1) training on aflatoxin and its prevention, (2) distribution of free drying sheets, and (3) a price premium for groundnuts that comply with aflatoxin regulations. We find that training farmers substantially improves post-harvest practices. Drying sheet distribution and, to a lesser extent, the premium price offer lead to further improvements, including crowding-in of non-subsidized practices. We find substantial corresponding decreases in aflatoxin levels from drying sheet provision in the study region with high background aflatoxin levels. Impacts are stronger for households with higher aflatoxin at baseline, more members, and young children.